UPAYA MENGEMBANGKAN SIKAP SPIRITUAL DAN SOSIAL PESERTA DIDIK BERBASIS PSIKOLOGI POSITIF DI SEKOLAH - Alivermana Wiguna (Universitas Muhammadiyah Ponorogo, 2017)
The condition of the spiritual and social attitude among the students, especially students in Indonesia are Muslim, presumably enough concern. If for a moment we see the condition of the Congregation to pray in the mosque and there was very rarely, mushalla teens ages junior high and senior high school students active in the prayer congregation. Similarly, in terms of social attitudes, it is not uncommon to cause conflict and strife, even to a brawl which led to the death. These conditions encourage the Government to incorporate aspects of spiritual and social attitudes as the must-have competencies in the curriculum learners 2013. It is, therefore, a problem that wants to be revealed in this study is what efforts should be done to develop the spiritual attitude of and social students? Among the efforts to develop the spiritual and social attitude of the learners is through positive psychology review. To develop attitudes of spirituality are: (1) familiarize prayer is Dhuhr Congregation; (2) organized a prayer Friday; (3) the movement comes to the mosque; (4) hold a prayer lesson matriculation and reading Qur'an. To develop the attitude of grateful are: (1) get used to say thanks; (2) make a list of grateful; (3) make a list of the names of the people who are supposed to be delivered thanks; (4) make thank you greeting cards; (5) class grateful; and (6) if I become. Whereas in order to develop the attitude of honesty are: (1) individual tasks or Deuteronomy honestly; (2) hold honesty. To develop the character of the apology were: (1) build self-awareness in students that the man did not escape the error: (2) write a letter of apology; and (3) organize apologizing class